Deep brain stimulation and climbing fiber synaptic pathology in essential tremor. Issue 3 (2nd August 2016) - Kuo, Sheng‐Han; Lin, Chi‐Ying; Wang, Jie; Liou, Jyun‐You; Pan, Ming‐Kai; Louis, Ravi J.; Wu, Wei‐Pu; Gutierrez, Jesus; Louis, Elan D.; Faust, Phyllis L.
Abstract : Essential tremor (ET) patients have abnormal climbing fiber (CF) synapses in the parallel fiber territory in the cerebellum, and these abnormal CF synapses are inversely correlated with tremor severity. We therefore examined CF synaptic pathology in ET cases with and without thalamic deep brain stimulation (DBS) and assessed the association with tremor severity. We found that CF synaptic pathology was inversely correlated with tremor severity in ET cases without DBS, and this correlation disappeared in ET cases with DBS. Our data suggest that DBS might have effects in modulating excitatory synapses in ET cerebellum, in addition to its symptomatic effects on tremor. Ann Neurol 2016;80:461–465